Stakeholder Perceptions of Age and Other Dimensions of Newness - Choi, Young Rok (Institutional Knowledge at Singapore Management University, 2010)
Using verbal protocol and conjoint analyses, this study examines how stakeholders assess an organization in deciding whether to provide their support to it. The authors find that stakeholdersÆ support depends on their perceptions of an organizationÆs age and other dimensions of newness related to addressing management challenges of adaptationùthe entrepreneurial problem, the engineering problem, and the administrative problem. Stakeholder support is more likely for those organizations that are old, cognitively legitimate, affectively congruent, reliable, accountable, and strategically flexible. The authors conclude with theoretical implications for scholars and practical implications for resource acquisition in various contexts of entrepreneurship.